MAKTABGACHA BO’LGAN YOSH DAVRLARIDA BOLALAR BILAN MULOQOT SHAKLLARI - Sadinova Marjona Akmal qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article describes the age characteristics of preschool children and forms of communication with them. The article is intended for teachers of MTT and students and parents.